This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: x ( t ) = Ke at + e at t Z e-a b ( ) d . SOLUTION OF THE INITIAL VALUE PROBLEM: Since x (0) = x o is the given initial condition and since x (0) = Ke + 0 = K , it follows that K = x o and the solution of the initial value problem is: x ( t ) = x o e at + e at t Z e-a b ( ) d . 2...
View Full Document
This note was uploaded on 12/02/2009 for the course MATH 352 taught by Professor Staff during the Spring '08 term at University of Delaware.
- Spring '08